Determining potential of subcooling to attenuate hydrodynamic instabilities for steam–water two phase flow. (May 2015) - Sanaullah, Khairuddin; Khan, Afrasyab; Takriff, Mohd Sobri; Zen, Hushairi; Shah, Ajmal; Chughtai, Imran Rafiq; Jamil, Tahir; Fong, Lim Soh; Haq, Noaman Ul
Abstract: Hydrodynamic instabilities are regarded as important but are undesirable occurrences for the systems used in process industries, which involve steam. These instabilities affect to a great extent the life line of the safe operation of their systems by inducing thermal stresses and steam induced water hammers. On the basis of system operational analysis, it was found that condensation induced hydrodynamic instabilities were responsible for one third of the destructive events in steam driven systems and their attributes in power and process industry. Thus it becomes vital to investigate the influence of critical parameter such as sub-cooling to curb the destructive effects due to hydrodynamic instabilities on to the process equipment. Here for steam water two phase flows, the attenuation of hydrodynamic instabilities due to sub-cooling and inlet pressure has been investigated. It was found that sub-cooling has more pronounced and notable effect on the attenuation of these instabilities.